Crimes against faith in De delictis reservatis Norms of 2010 - BOREK, DARIUSZ (Prawo Kanoniczne, 2014)
De Delictis reservatis norms issued in the year 2010 state that crimes against faith, such as heresy, apostasy and schism, come within the Congregation for the Doctrine of the Faith jurisdiction. The fact that these crimes are the first to be listed in the present norms emphasises the gravity of the offences as the ones particularly hurting the unity of the Body of Christ. In the present article, entitled "Crimes against faith in De delictis reservatis norms of 2010, only the issues concerning the objective and subjective side of the crimes against faith are analysed. From the objective point of view there are various forms of crimes against faith, starting from the complete abandoning of the Christian faith, through losing the Catholic faith, to the breaking with the Catholic Church as a result of rupture with the Bishop of Rome. However, it should be emphasised that to commit a crime of apostasy, heresy or schism it is necessary to both manifest heretical or schismatical will and to have that declaration of will understood and accepted. The crimes against faith belong to delicta communia category, which means that all the faithful belonging to the Catholic Church can be their perpetrators. It should be remembered that the ecclesiastical affiliation coming from baptism cannot be annihilated even by a formal act of leaving the Church. From the subjective point of view it is also essential for those crimes to be committed with intentional guilt. This means that they must be a result of conscious and voluntary action intended to commit a specific crime. Thus a conscious intention to commit an unlawful act is a vital element of intentional guilt. While determing criminal responsibility for crimes against faith, one should keep in mind whether a given violation bears all the hallmarks of a specific form of offences against faith. Moreover, it is significant to attribute that violation to the perpetrator as a result of dolus, that is intentional guilt.